THE EFFECT OF PROPANOLOL ON C-REACTIVE PROTEIN IN PATIENTS WITH SEVERE BURNS AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - U H, Muhammad Aulia; Saputro, Iswinarno Doso; Hutagalung, Magda Rosalina (Jurnal Rekonstruksi dan Estetik, 2019)
Highlights: The biochemical marker of inflammation and suggests a potential mechanism through which propranolol affects hypermetabolism in burn patients. The administration of propranolol giving effectivity of hypermetabolism which is characterized by decreasing in CRP levels.   Abstract: Introduction: The incidence of burns in Indonesia progressively  increases with the increase in its population and industries. From January to September 2000, 158 patients were treated in the burn unit of Dr. Soetomo General Academic Hospital with a mortality rate reaching 5.8%. Burns have a direct effect in causing both local and systemic changes in the body, not occurring in other injuries. In severe burns, a hypermetabolic state can occur, which increases cardiac workload and causes muscle atrophy and other morbidities. The purpose of this study is to examine the effect of propranolol on the hypermetabolic state in severely burned patients by measuring various clinical & laboratory parameters. Methods: This is an experimental study using pre and post test control group design with the objective of assessing the treatment outcome with oral propranolol given in 15 consecutive days for burn patients involving 25%- 60% TBSA. Measurements were taken three times, on day 0.7 and 14. Discussion: Obtained 16 samples divided into 2 groups. In the treatment group, there was a significant decrease in CRP levels on days 0.7 and 14 (p <0.05). The Mid Arm Circumference variable did not obtain a significant decreasing on days 0.7 and 14. The albumin level studied showed a significant decreasing on day 0 & 7 days with a value of p=0.045. From the comparison between the two groups, there were significant differences in CRP levels on days 0 & 14, with the mean value of the treatment group -5.12 + 2.88 and the mean value of the control group 2.86 + 7.37, and the value of p = 0.019. Conclusions: This study successfully proved that the administration of propranolol can overcome the effects of hypermetabolism which is characterized by decreasing in CRP levels.